An experimental approach to delineate the reaction mechanism of Ti3AlC2 MAX-Phase formation. Issue 8 (July 2023) - Yunus, Mohammad; Maji, Bikas C.
Abstract: A comprehensive reaction mechanism of Ti3 AlC2 MAX-phase formation from its elemental powders while spark plasma sintering has been proposed. Microstructural evaluation revealed that Al-rich TiAl3 intermetallic forms at around 660 °C once Al melts. Gradual transition from TiAl3 to Ti-rich TiAl and Ti3 Al intermetallic phases occurs between 700 °C and 1200 °C through formation of layered structure due to diffusion of Al from periphery toward the centre of Ti particles. Formation of TiC and Ti3 AlC transient carbide phases were observed to occur through two different reactions beyond 1000 °C. Initially, TiC forms due to interaction of Ti and C, which further reacts with TiAl and Ti and gives rise to Ti3 AlC. Later, Ti3 AlC also forms due to diffusion of C into Ti3 Al above 1200 °C. Above 1300 °C, Ti3 AlC phase decomposes into Ti2 AlC MAX-phase and TiC in presence of unreacted C. Finally, Ti2 AlC and TiC reacts together to from Ti3 AlC2 MAX-phase above 1350 °C and completes at 1500 °C.